Ibuprofen‐Loaded Poly(Lactic Acid) Electrospun Mats: The Morphology, Physicochemical Performance, and In Vitro Drug Release Behavior. Issue 12 (4th November 2020) - Sun, Chenkai; Zou, Liming; Xu, Yongjing; Wang, Yanli
Abstract: To solve the problems of limited drug solubility and poor biodistribution with polymers in drug delivery system, ibuprofen (IBU) is chosen to prepare IBU‐loaded poly(lactic acid) (PLA) micro‐fibrous mats via electrospinning. Distinguished from the previous studies, a lower toxic binary solvent dichloromethane/ethanol (DCM/EtOH, v / v  = 8/2) is used to successfully fabricate PLA/IBU electrospun mats with outstanding properties. In order to further evaluate the effects of IBU content on PLA, there are characterization methods employed as follows: scanning electron microscopy (SEM), Fourier‐transform infrared (FTIR) spectroscopy, X‐ray diffraction (XRD), differential scanning calorimetry (DSC), and UV–vis spectrophotometer. The results show that IBU can be physically and uniformly distributed both on the surface and inside of PLA fibers. Compared with pure PLA mats, the crystallinity and mechanical properties of PLA/IBU electrospun mats has significantly improved. Meanwhile, in vitro drug release behavior demonstrates that with the increasing content of IBU, the rate of IBU release has increasingly improved. Particularly, the release behavior of PLA/IBU mats exhibited best with 20% IBU content, and the release amount reached 74.3% at the end of 240 h. Considering all these features, PLA/IBU electrospun mats have the potential to be used in the fields of wound dressing and drug delivery. Abstract : Ibuprofen (IBU)‐loaded poly(lactic acid) (PLA) micro‐fibrous mats are successfully prepared via electrospinning using a lower toxic binary solvent dichloromethane/ethanol (DCM/EtOH, v / v  = 8/2). Particularly, the influence of IBU content on the physicochemical properties and in vitro drug release behavior are investigated. The results show that PLA/IBU mats have the potential to be used in the fields of wound dressing and drug delivery system.